Randomly barcoded transposon mutant libraries for gut commensals I: Strategies for efficient library construction - Surya Tripathi; Carlos Geert Pieter Voogdt; Stefan Oliver Bassler; Mary Anderson; Po-Hsun Huang; Nazgul Sakenova; Tümay Capraz; Sunit Jain; Alexandra Koumoutsi; Afonso Martins Bravo; Valentine Trotter; Michael Zimmerman; et al. (Cell Reports, 2024)
Summary: Randomly barcoded transposon mutant libraries are powerful tools for studying gene function and organization, assessing gene essentiality and pathways, discovering potential therapeutic targets, and understanding the physiology of gut bacteria and their interactions with the host. However, construction of high-quality libraries with uniform representation can be challenging. In this review, we survey various strategies for barcoded library construction, including transposition systems, methods of transposon delivery, optimal library size, and transconjugant selection schemes. We discuss the advantages and limitations of each approach, as well as factors to consider when selecting a strategy. In addition, we highlight experimental and computational advances in arraying condensed libraries from mutant pools. We focus on examples of successful library construction in gut bacteria and their application to gene function studies and drug discovery. Given the need for understanding gene function and organization in gut bacteria, we provide a comprehensive guide for researchers to construct randomly barcoded transposon mutant libraries.